Selective Polygraphy and Resonant Stimulation of Digestive Tract in Early Postoperative Period in Peritonitis - I. G. Bobrinskaya; V. V. Moroz; V. N. Yakovenko; O. N. Kudryakov; E. A. Spiridonova; V. Y. Soldatova (Общая реаниматология, 2016)
The aim of the study was to demonstrate the effectiveness of the method of selective polygraphy and resonance stimulation of gastrointestinal tract (GIT) in the complex intensive therapy in early postoperative period in a patient with acute intestinal obstruction complicated by peritonitis.Materials and methods. The patient L., female, 52 years old, had numerous operations, because of small intestine obstruction complicated by serousfibrinous peritonitis in early postoperative period (7 days after the first surgery). Patient was performed with a longlasting diagnosis procedure followed by the GIT resonant stimulation to restore the motorevacuation function of GIT. An electrogastroenterography device was employed that was approved for clinical use by the Ministry of Healthcare Industry № 226819, 1998).Results. The amplitude of the oscillations due to resonant effects on the excitable structures gradually increased from 8—22 mkV to 20—44 mkV that indicates the increase of the numbers of passive structures in smooth muscles of the stomach and the jejunum). At the end of three final sessions the amplitudes of the signals (specific reactions) demonstrated the following values: 93 mkV, 88 mkV, 90 mkV, 87 mkV (for the stomach, duodenum, jejunum and ileum, and large intestines, respectively).Conclusion. These values and activity after the stimulation corresponded to the normal GIT motility.